2021
DOI: 10.1021/acs.jafc.0c07894
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Odor-Active Compounds of Ichang Lemon (Citrus wilsonii Tan.) and Identification of Its Genetic Interspecific Origin by DNA Genotyping

Abstract: Ichang lemon is a citrus fruit whose rind gives off a delicious and much appreciated fragrance and flavor. The volatile components of the fruit peel of Ichang lemon were investigated by GC-MS and GC-O (AEDA method). Simultaneously, its genetic origin was identified by using diagnostic SNP markers specific to ancestral species and multiallelic SSR and InDel markers. Ichang lemon combines three ancestral genomes (Citrus maxima, Citrus ichangensis, and Citrus reticulata) and may be a pummelo × Yuzu hybrid. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Peel oils of C. wilsonii, C. junos, and C macrophylla were characterized by high limonene contents (66.9, 79.9, and 81.4%, respectively), and were associated with noticeable amounts of γ-terpinene (10.1, 8.8, and 5.0%, respectively). The chemical composition of C. wilsonii peel oil was close to one previously reported from a hexane extract, which contained limonene (56.6%), γ-terpinene (17.8%), β-phellandrene (3.8%), β-pinene (2.4%), linalool (1.6%), and myrcene (1.3%) [7]. In this study, the authors concluded that C. wilsonii combined three ancestral genomes (C. maxima, C. ichangensis, and C. reticulata) and may be a pummelo × Yuzu hybrid.…”
Section: Related Speciessupporting
confidence: 82%
See 2 more Smart Citations
“…Peel oils of C. wilsonii, C. junos, and C macrophylla were characterized by high limonene contents (66.9, 79.9, and 81.4%, respectively), and were associated with noticeable amounts of γ-terpinene (10.1, 8.8, and 5.0%, respectively). The chemical composition of C. wilsonii peel oil was close to one previously reported from a hexane extract, which contained limonene (56.6%), γ-terpinene (17.8%), β-phellandrene (3.8%), β-pinene (2.4%), linalool (1.6%), and myrcene (1.3%) [7]. In this study, the authors concluded that C. wilsonii combined three ancestral genomes (C. maxima, C. ichangensis, and C. reticulata) and may be a pummelo × Yuzu hybrid.…”
Section: Related Speciessupporting
confidence: 82%
“…One of the main characteristics of Citrus is the presence of highly aromatic essential oils in tissue storage cells of the fruit, leaf, and flower (petals). These essential oils are complex mixtures that can contain hundreds of compounds with a very wide chemical diversity, which is prized by the aromatic and cosmetic industry [7]. The composition of essential oils in the majority of citrus fruits grown for consumption is very well documented [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research, six tea cultivars with good cold-resistance and productivity were selected in this study, such as Baihaozao, Jinxuan, Longjing Changye Zhongcha 302, Yingshuang and Huangshan Qunyizhong [18,19]. The aroma compounds were analyzed by headspace solid phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC-MS) combined with gas chromatography-olfactometry (GC-O), which was widely applied in fruits, foods and other fields for its high efficiency and convenience [7,20,21]. This study would provide a theoretical basis for the processing of high-latitude black tea improved its poor quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies confirmed that CWT was an offspring of Yuzu by molecular markers (Shimizu et al, 2016). Further researches speculated that CWT might be a pummelo × Yuzu hybrid, and pummelo might be the maternal parent (Demarcq et al, 2021).…”
Section: Introductionmentioning
confidence: 94%